PUBLIC SERVICES IN THE FIELD OF LEGAL AID FOR UNDERPRIVILEGED COMMUNITIES - Mochamad. Riyanto; Mohammad Solekhan; Rini Retnowinarni (Sean Institute, 2023)
Public services in the legal aid field for underprivileged people facing legal problems is a constitutional obligation based on the 1945 Constitution. Through legal instruments and/or regulations within the scope of the linkages of laws and regulations, it is perceived that they are complete, significantly as imperatively regulated in Law Number 25 of 2009 concerning Public Services and Law Number 16 of 2011 concerning Legal Aid. Regulatory arrangements related to public services in the legal aid field are clearly regulated within the scope of the authority of the Menkumham through National Legal Development Agency (BPHN). Procedures for filing legal aid. Institutions that are given the authority to provide legal assistance on condition that they have been accredited by the Ministry of Law and Human Rights, criteria that have the right to obtain legal aid services. In this study, researchers have taken a normative juridical approach by describing procedures for providing public services in the field of legal aid and the instruments and/or regulations that cover them or regulate them for the purpose of fulfilling the principles of legal certainty, legal justice and legal benefits for underprivileged people who face law problem.